Influence of Aging on the Retina and Visual Motion Processing for Optokinetic Responses in Mice - Sugita, Yuko; Yamamoto, Haruka; Maeda, Yamato; Furukawa, Takahisa (Frontiers in Neuroscience, 2020)
The decline in visual function due to normal aging impacts various aspects of our daily lives. Previous reports suggest that the aging retina exhibits mislocalization of photoreceptor terminals and reduced amplitudes of scotopic and photopic electroretinogram (ERG) responses in mice. These abnormalities are thought to contribute to age-related visual impairment; however, the extent to which visual function is impaired by aging at the organismal level is unclear. In the present study, we focus on the age-related changes of the optokinetic responses (OKRs) in visual processing. Moreover, we investigated the initial and late phases of the OKRs in young adult (2–3 months old) and aging mice (21–24 months old). The initial phase was evaluated by measuring the open-loop eye velocity of OKRs to sinusoidal grating patterns of various spatial frequencies (SFs) and moving at various temporal frequencies (TFs) for 0.5 s. The aging mice exhibited initial OKRs with a spatiotemporal frequency tuning that was slightly different from those in young adult mice. The late-phase OKRs were examined by measuring the slow-phase velocity of the optokinetic nystagmus induced by sinusoidal gratings of various spatiotemporal frequencies moving for 30 s. We found that optimal SF and TF in the normal aging mice are both reduced compared with those in young adult mice. In addition, we measured the OKRs of 4.1G-null (4.1G−/−) mice, in which mislocalization of photoreceptor terminals is observed even at the young adult stage. We found that the late phase OKR was significantly impaired in 4.1G−/− mice, which exhibit significantly reduced SF and TF compared with control mice. These OKR abnormalities observed in 4.1G−/− mice resemble the abnormalities found in normal aging mice. This finding suggests that these mice can be useful mouse models for studying the aging of the retinal tissue and declining visual function. Taken together, the current study demonstrates that normal aging contributes to visual motion processing for both the initial and late phases of OKRs. Moreover, it implies that the abnormalities of the visual function in the normal aging mice are at least partly due to ectopic synapse formation.